AcrB, AcrD, and MdtABC Multidrug Efflux Systems Are Involved in Enterobactin Export in Escherichia coli - Horiyama, Tsukasa (Public Library of Science, 2014)

(untitled)
Escherichia coli produces the iron-chelating compound enterobactin to enable growth under iron-limiting conditions. After biosynthesis, enterobactin is released from the cell. However, the enterobactin export system is not fully understood. Previous studies have suggested that the outer membrane channel TolC is involved in enterobactin export. There are several multidrug efflux transporters belonging to resistance-nodulation-cell division (RND) family that require interaction with TolC to function. Therefore, several RND transporters may be responsible for enterobactin export. In this study, we investigated whether RND transporters are involved in enterobactin export using deletion mutants of multidrug transporters in E. coli. Single deletions of acrB, acrD, mdtABC, acrEF, or mdtEF did not affect the ability of E. coli to excrete enterobactin, whereas deletion of tolC did affect enterobactin export. We found that multiple deletion of acrB, acrD, and mdtABC resulted in a significant decrease in enterobactin export and that plasmids carrying the acrAB, acrD, or mdtABC genes restored the decrease in enterobactin export exhibited by the ΔacrB acrD mdtABC mutant. These results indicate that AcrB, AcrD, and MdtABC are required for the secretion of enterobactin.